2020
DOI: 10.1186/s40575-020-00083-x
|View full text |Cite
|
Sign up to set email alerts
|

Moving from information and collaboration to action: report from the 4th international dog health workshop, Windsor in May 2019

Abstract: Background: Dogs are the most popular mammal kept as a companion animal globally. Positive human-dog relationships can benefit both the human owners as well as the dogs. However, popularity as a companion animal species does not universally benefit dogs in reverse. Breed-related health problems in dogs have received increasing attention over the last decade, sparking increased concerns for dog welfare across many stakeholders. Progress towards improved welfare requires meaningful collaboration between all thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Rather than CI alone, pre-existing perceptions of the breeds used in the current study may have affected EA. However, this is unlikely to explain the current results fully, because the Staffordshire Bull Terrier, which in this study was represented in two of the three MC dog images, has suffered negative press in the U.K. [ 51 ] even though current MC images were rated the most positively, implying breed perception did not significantly influence EA, or that these views are variable in the public [ 52 ]. In 2013, McGreevy et al [ 30 ] reported that eight undesirable behavioural traits correlated with CI, half of which correlated positively and half negatively.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than CI alone, pre-existing perceptions of the breeds used in the current study may have affected EA. However, this is unlikely to explain the current results fully, because the Staffordshire Bull Terrier, which in this study was represented in two of the three MC dog images, has suffered negative press in the U.K. [ 51 ] even though current MC images were rated the most positively, implying breed perception did not significantly influence EA, or that these views are variable in the public [ 52 ]. In 2013, McGreevy et al [ 30 ] reported that eight undesirable behavioural traits correlated with CI, half of which correlated positively and half negatively.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first Dog Health Workshop was arranged in Stockholm in 2012, multi-stakeholders with an interest in canine health have met and created the International Partnership for Dogs and DogWellNet, focusing on various aspects of canine health, including extreme conformation [5]. The stakeholders have gathered repeatedly with exaggerated features as one theme [6,7] and have established an International Collaborative on Extreme Conformation in Dogs (ICEC Dogs) [8]. A textbook with an extensive review and references to activities regarding BOAS was published in 2021 [9].…”
Section: Introductionmentioning
confidence: 99%
“…The International Partnership for Dogs (IPFD) has concluded that multi-stakeholder engagement is required to combat dog welfare challenges, including engagement between DWOs, kennel clubs, state services, veterinarians, and dog owners [ 12 ]. Additionally, the breed-specific strategies for health and breeding, supply and demand and behaviour were prominent themes in their report.…”
Section: Introductionmentioning
confidence: 99%